2012
DOI: 10.1007/s00167-012-1968-8
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic extraarticular reconstruction of the medial patellofemoral ligament with gracilis tendon autograft - surgical technique

Abstract: The standard approach to reconstruct the medial patellofemoral ligament (MPFL) is by mini-open incision at its patellar insertion and femoral origin. At the medial patella rim, the MPFL insertion may be visualized in most cases by dissection during surgery. On the femur, it is more difficult to localize the MPFL remnants by a mini-open incision due to soft tissue covering the anatomical origin. Therefore, the femoral MPFL origin is usually identified by intraoperative lateral fluoroscopy. However, the insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 43 publications
(114 reference statements)
1
30
0
Order By: Relevance
“…Many techniques are used to accomplish this, and various graft options have been described, including semitendinosus, 18-29 patellar tendon, 30,31 partial quadriceps tendon, 30,32 adductor magnus, 6,30,33 gracilis, 9,15,[34][35][36][37] and iliotibial band grafts 38 ; allografts 12,30,39 ; and synthetic grafts. 17,40,41 Methods for patellar fixation vary as well and include tunnels with interference screws 12,22,39 ; single 40,42,43 and double 34,44 through-and-through tunnels with looped, knotted, 17 or soft-tissue suture fixation 6,20,21 ; V-shaped converging tunnels 35,45 ; double diverging tunnels 24 ; anchor fixation 23 ; and soft-tissue sutures.…”
Section: See Commentary On Page 1381mentioning
confidence: 99%
“…Many techniques are used to accomplish this, and various graft options have been described, including semitendinosus, 18-29 patellar tendon, 30,31 partial quadriceps tendon, 30,32 adductor magnus, 6,30,33 gracilis, 9,15,[34][35][36][37] and iliotibial band grafts 38 ; allografts 12,30,39 ; and synthetic grafts. 17,40,41 Methods for patellar fixation vary as well and include tunnels with interference screws 12,22,39 ; single 40,42,43 and double 34,44 through-and-through tunnels with looped, knotted, 17 or soft-tissue suture fixation 6,20,21 ; V-shaped converging tunnels 35,45 ; double diverging tunnels 24 ; anchor fixation 23 ; and soft-tissue sutures.…”
Section: See Commentary On Page 1381mentioning
confidence: 99%
“…4,6 The importance of this ligament in chronic lateral patellar instability in a patient with normal osseous anatomy and limb alignment has led to the development of various surgical techniques to reconstruct the MPFL with variations in graft choice, anatomic versus nonanatomic reconstruction, and fixation methods. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Several studies have shown the importance of an anatomic reconstruction of the femoral attachment. 34,35,38 A femoral tunnel that is too proximal may lead to graft laxity in extension and over-tensioning in flexion, a femoral tunnel that is too distal may lead to graft over-tensioning in extension and laxity in flexion, and tunnel placement too anterior can cause overloading of the medial patellofemoral cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Because of its importance, various techniques have been described to reconstruct the MPFL in chronic lateral patellar instability. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The purpose of this Technical Note and accompanying video (Video 1) is to describe an MPFL reconstruction technique that uses a patella dual docking tunnel technique to create an anatomic reconstruction.…”
mentioning
confidence: 99%
“…Another advantage of the fascia lata in contrast to the most frequently used grafts for MPFL reconstruction, that is, the gracilis, quadriceps, or semitendinosus tendon, lies in the comparable shape and biomechanical similarity to the native MPFL. 32 , 33 , 34 The gracilis or semitendinosus tendon's shape can be considered tubular and longer than needed, whereas the fascia lata presents the shape of an aponeurosis. 35 , 36 A biomechanical study has recently shown that cordlike grafts cannot completely replace the MPFL's natural functional behavior.…”
Section: Discussionmentioning
confidence: 99%